Dismal Survival in COVID-19 Patients Requiring ECMO as Rescue Therapy after Corticosteroid Failure - Sebastian Voicu (MDPI AG, 2021)
(1) Background: COVID-19 may lead to refractory hypoxemia requiring venovenous extracorporeal membrane oxygenation (ECMO). Survival rate if ECMO is implemented as rescue therapy after corticosteroid failure is unknown. We aimed to investigate if ECMO implemented after failure of the full-recommended 10-day corticosteroid course can improve outcome. (2) Methods: We conducted a three-center cohort study including consecutive dexamethasone-treated COVID-19 patients requiring ECMO between 03/2020 and 05/2021. We compared survival at hospital discharge between patients implemented after (ECMO-after group) and before the end of the 10-day dexamethasone course (ECMO-before group). (3) Results: Forty patients (28M/12F; age, 57 years (51–62) (median (25th–75th percentiles)) were included, 28 (70%) in the ECMO-before and 12 (30%) in the ECMO-after group. In the ECMO-before group, 9/28 patients (32%) received the 6 mg/day dexamethasone regimen versus 12/12 (100%) in the ECMO-after group (p < 0.0001). The rest of the patients received an alternative dexamethasone regimen consisting of 20 mg/day during 5 days followed by 10 mg/day during 5 days. Patients in the ECMO-before group tended to be younger (57 years (51–59) versus 62 years (57–67), p = 0.053). In the ECMO-after group, no patient (0%) survived while 12 patients (43%) survived in the ECMO-before group (p = 0.007). (4) Conclusions: Survival is poor in COVID-19 patients requiring ECMO implemented after the full-recommended 10-day dexamethasone course. Since these patients may have developed a particularly severe presentation, new therapeutic strategies are urgently required.